El traductor visible de literatura poscolonial ante la tentación del exotismo - López Heredia, Goretti (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
Building upon The Translator’s Invisibility by L. Venuti and related work by Susan Bassnett, Ovidi Carbonell, Anuradha Dingwaney, Samia Mehrez and Mahasweta Sengupta, among others, this paper argues for the visibility of the postcolonial literature translator and draws a carefull line between proper visibility – as we define it – and a counterproductive exotism that may arise as the side-product of a poorly understood visibility. Our discussion focuses on the particular case of postcolonial lusophone African literature. In particular, we analyze the translation strategy adopted by the author of this paper for the translation from portuguese to catalan of A Varanda do Frangipani, a novel by Mia Couto from Mozambique.